2008
DOI: 10.3136/fstr.14.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclodextrins on the Thermal Epimerization of Tea Catechins

Abstract: The epimerization reaction of tea catechins was investigated at pH 5.5 and 120 °C in the absence/presence of cyclodextrins (CDs). In the absence of CDs, a considerable quantity (~20%) of products originating from reactions other than the epimerization ("other products") was formed during the epimerization of gallated catechins. In the case of (-)-EGCg, addition of β-CD to the reaction solution reduced the quantity of these other products to just a few percent, but other CDs with different cavity sizes had litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The predominant reactions of catechins during exposure to heat appear to be isomerization and autooxidation (Komatsu et al 1993. Isomerization of epicatechins to their nonepi isomers is thermodynamically favorable (Okumura et al 2008). The heats of formation ( H f ) of the nonepi isomers are 1-2 kcal mol −1 lower than those of epi forms, and this difference is sufficient to drive epimerization during typical thermal processes (Okumura et al 2008).…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant reactions of catechins during exposure to heat appear to be isomerization and autooxidation (Komatsu et al 1993. Isomerization of epicatechins to their nonepi isomers is thermodynamically favorable (Okumura et al 2008). The heats of formation ( H f ) of the nonepi isomers are 1-2 kcal mol −1 lower than those of epi forms, and this difference is sufficient to drive epimerization during typical thermal processes (Okumura et al 2008).…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Isomerization of epicatechins to their nonepi isomers is thermodynamically favorable (Okumura et al 2008). The heats of formation ( H f ) of the nonepi isomers are 1-2 kcal mol −1 lower than those of epi forms, and this difference is sufficient to drive epimerization during typical thermal processes (Okumura et al 2008). The significance of thermally induced isomerization is reflected in studies demonstrating that retorted green tea beverages contain (−)-GCG as their predominant catechin species, whereas (−)-EGCG is the predominant species present in unprocessed green tea (Chen et al 2001, Zhu et al 2003.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Previously, we reported on the UV absorption spectra of green tea catechins and showed that gallated and nongallated catechins exhibited quite different pH dependence (Okumura et al, 2007). As shown in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…This peak corresponds to ultra high MWs that exceed the GPC column size exclusion limit of approximately 600,000. Thus, the sample contains very high molecular weight gel components.Previously, we reported on the UV absorption spectra of green tea catechins and showed that gallated and nongallated catechins exhibited quite different pH dependence (Okumura et al, 2007). As shown in Fig.…”
mentioning
confidence: 81%
“…However, as green tea catechins are characterized by strong bitterness and astringency, the development of products that can be consumed regularly is necessary for their efficient, routine intake. To date, research papers and patents concerning processing techniques, such as the masking of bitterness and astringency using cyclodextrin (Okumura et al, 2008(Okumura et al, , 2009Hayashi et al, 2010) and the suppression of bitterness and astringency with the addition of chitosan complex and soy milk protein, have been reported. However, the intrinsic taste and flavor of green tea may be impaired and the cost of manufacturing may be increased due to additives such as protein and chitosan.…”
Section: Introductionmentioning
confidence: 99%